Pemanfaatan Hasil Olahan Pertanian Berbasis Masjid - Fahmi Irfanuddin; Fathurrahman Kamal; Cahyo Setiadi Ramadhan (Universitas Muhammadiyah Yogyakarta, 2019)
The Regency of Kulon Progo has tourism and agriculture potentials. The same condition also applies to Jatimulyo village which is one of the villages in Kulon Progo. Jatimulyo has a good agriculture potential, such as aren (sugar palm). Jatimulyo has recently been developing after the access from the village to the city center had become better. As such, the society of the area needs to be encouraged to better improve. The society’s potential that can be developed is business with the basis of processed agricultural products. To realize the goal, various society’s empowerment programs are held to promote the society’s awareness on distribution method so that their agricultural products can be competitive and can gain optimum profit. The programs are held through the methods of counseling, recitation, and a provision of stimulating fund. The results from the counseling given to mosque basis partners are transfer of knowledge on the urgency of processed agricultural products, farming group at Gunung Kelir, and variations of processed agricultural products.